2020
DOI: 10.14198/jhse.2021.162.02
|View full text |Cite
|
Sign up to set email alerts
|

Motor coordination and academic performance in primary school students

Abstract: Objective: There is interest in studying the relationship between cognition and motor skills for decades. However, there are few studies that provide scientific evidence on the relationship between motor coordination and academic performance. Therefore, a descriptive cross-sectional study was conducted with 163 Spanish schoolchildren aged 6-9 years. Motor coordination was measured with the GRAMI-2 Test. Academic performance was obtained through the average grades of the subjects of language, mathematics, natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
1
14
0
7
Order By: Relevance
“…The results of the study by Abdelkarim et al [ 13 ] lead to a conclusion that encouraging motor competence in the prepubescent children during their elementary school years is associated with better academic achievement. This was confirmed by several other studies indicating the positive effects of motor competence on academic achievement [ 7 , 12 , 14 20 ]. Regarding physical fitness, Sardinha et al [ 21 ] showed in their longitudinal study that an improvement in fitness in children increases the probability of higher academic achievement.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the study by Abdelkarim et al [ 13 ] lead to a conclusion that encouraging motor competence in the prepubescent children during their elementary school years is associated with better academic achievement. This was confirmed by several other studies indicating the positive effects of motor competence on academic achievement [ 7 , 12 , 14 20 ]. Regarding physical fitness, Sardinha et al [ 21 ] showed in their longitudinal study that an improvement in fitness in children increases the probability of higher academic achievement.…”
Section: Introductionsupporting
confidence: 86%
“…Having in mind that the development of motor skill competence is a primary underlying mechanism that promotes engagement in physical activity and fitness [ 11 ], we think that similar relationship between motor competence, physical fitness, and academic achievement was logical. However, studies that examined the association between physical activity, motor competence and physical fitness, and academic achievement showed contradictory results, especially in the directionality of association [ 12 ]. Apart from this well-known effect, a large number of authors produced research on the effect of the level of motor skills on the cognitive abilities and academic achievement in the children.…”
Section: Introductionmentioning
confidence: 99%
“…These might be explained by the fact that the coordinative component of the movement increases synapses in important brain areas such as the cerebellum ( Donnelly et al, 2016 ). Complex movement patterns engage the cerebellum which affects areas such as attention and memory, functions that are affected by cerebellum ( Guillamón et al, 2020 ). Specifically, visuospatial attention is important in the performance of a variety of activities and plays a central role for processing visual information and perceiving moving stimuli ( Guo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, visuospatial attention is important in the performance of a variety of activities and plays a central role for processing visual information and perceiving moving stimuli (Guo et al, 2016). A series of studies support the idea that physical exercise make children and adolescent more efficient than sedentary, in attention-orientation tasks (Guillamón et al, 2020). Similarly, working memory, that is the ability to maintain and consciously manipulate information, is particularly age-sensitive (Baddeley et al, 1999;Kirova et al, 2015) and seems to be particularly flexible at a younger ages.…”
Section: Introductionmentioning
confidence: 99%
“…Zetou et al, conducted a study on the effect of coordination training on their tennis skills by doing 5minute coordination skills before tennis training for 4 drills for 8 weeks (athletes with a 1-year tennis background), they concluded that it has a positive effect on skill learning (p < 0.05) 31 .Guillamon et al, in their research examining the relationship between academic performance and motor coordination skills of 6-9 year old students, determined that there is a direct relationship. It was concluded that students with good academic performance also have a better motor coordination skills.It has been stated that the increase in physical activity opportunities can support the academic development of students 32 .…”
Section: Discussionmentioning
confidence: 99%